O processo de variação das palatais lateral e nasal no português de Belo Horizonte - Neffer Luiza de Aguiar Pinheiro (2009)
The present paper analyzes the behavior of the palatal lateral and the palatal nasal variables in the spoken Portuguese of Belo Horizonte (Minas Gerais). This research aims to observe the factors that influence the variability of the speech, taking into account the Variationist Theory (LABOV, 1972) and the Lexical Diffusion Model (WANG, 1969). Theanalyzed variable processes in relation to the behavior of the palatal lateral encompass: a) its realization in the standard form; b) its vocalized realization; c) realization as alveolar palatal; d) the variable erasure. The processes related to the palatal nasal encompass: a) its realizationin the standard form; b) its vocalized realization; c) the variable erasure, with the nasalization of the previous vowel; d) the variable erasure; e) its realization as im. In order to study such processes, a corpus constituted of 4,778 occurrences (1,624 referent to the lateral palatal; and 3,154 referent to the palatal nasal) was collected through interviews made with 24 informants of the studied speech community. The linguistic factorsthat were taken into consideration were the preceding and succeeding contexts, stress, number of syllables and diminishing morpheme, in the case of the palatal nasal. Both analyses researched the influence of the lexical item factor. The social factors analyzed were gender, age, social group and, in the case of the palatal lateral, education background.In relation to the analysis of the data referent to the palatal lateral, the results showed the influence of the lexical items and the social group in the realization of the vocalizedvariant. The analysis of the palatal nasal showed that is influenced by structural factors. The analysis allowed concluding that the variation process of the lateral and nasalpalatal in Belo Horizonte presents divergent directions. As the palatal lateral tends to remain as palatal, especially because its vocalized realization is socially stigmatized, the palatal nasal follows a process of articulation reduction, being easily depalatalized.